Irrigação suplementar do algodoeiro com água residuária tratada sob condições semiáridas: respostas fisiológicas, produtividade e análise econômica - Araújo, Antonio Flávio Batista de (2022)
Crop frustration due to water deficit in the Brazilian semi-arid region in the rainy season, almost always characterized by prolonged dry spells, has compromised the production and agricultural productivity of crops under rainfed conditions in the Brazilian semi-arid region. The use of wastewater treated in sewage treatment plants in supplementary irrigation, emerges as a strategy to increase agricultural production in a sustainable way during the rainy season, eliminating, at least partially, the losses associated with dry spells. In this context, the present work aimed to evaluate the impacts of supplementary irrigation with treated wastewater on cotton, with and without chemical fertilization, simulating soil moisture conditions based on a historical series of precipitation data over the last 30 years. during the months of February to May for the region of Baixo Jaguaribe-CE, considering normal, dry and severe drought scenarios. The research was carried out during the period of August-December 2020 in an area neighboring the ETE Sewage Treatment Station of Cagece Companhia de Agua e Esgoto do Estado do Ceará in the Municipality of Russas CE, under the geographic coordinates: S, 37 33 W, and altitude 20.51m. The trial was set up in a randomized block design, with treatments arranged in sub-subdivided plots, with four replications. The plots were formed by water scenarios (normal, dry and severe drought), defined based on a 30-year historical series of data. The subplots were composed by supplementation or not with treated wastewater, with the blades applied in dry spells (at least 5 days without rain). The subsubplots were formed by the presence or absence of NPK fertilization. Seeds of the BRS 433 B2RF cultivar were sown at 0.7m spacing between rows and 0.3m between holes, with two plants per hole. The results obtained point to the effectiveness of supplementary irrigation with wastewater throughout the vegetative and reproductive cycle of cotton, minimizing the risks of crop failure, enhancing rainfed agriculture in semi-arid regions. The irrigation depth supplementation with wastewater was beneficial to cotton mainly in simulated water regimes (dry and severe drought). Fertilization in treatments that received supplementation with wastewater did not provide an increase in foliar photosynthetic responses, demonstrating that supplementation by itself is already beneficial to the physiology of the cotton plant, proving the fertilizer potential of wastewater in substitution of chemical fertilization based on NPK.